Pengembangan Video Interaktif Persamaan dan Pertidaksamaan Linier Satu Variabel kelas VIII Berbasis Android - Kamelia, Nila Sa'idah; Farisi, Olief Ilmandira Ratu (Universitas Muhammadiyah Gresik, 2025)
The aim of this research is to provide an Android based interactive video for the VIII grade that focuses on linear equations and inequalities in one variable. ADDIE (Analysis, Design, Development, Implementation, Evaluation) models is implemented in developing this media. After the media has been developed using GDevelop, a validation stage is carried out with experts and trials are carried out with students. Material experts' percentage results meet the